Relationship of Sodium Reabsorption and Glomerular Filtration Rate to Renal Glucose Reabsorption - Kurtzman, Neil A. (1972)
Glucose reabsorption was measured in dogs in which sodium reabsorption was stimulated by obstruction of the thoracic inferior vena cava or inhibited by volume expansion with Ringer's lactate. Glucose reabsorption was much higher during periods of enhanced sodium reabsorption than during sodium diuresis. The relationship of glucose reabsorption to glomerular filtration rate was examined using data from animals that had fractional sodium excretion rates of less than 1%. Under this condition the relationship of glucose reabsorption to glomerular filtration rate is highly linear. When points obtained during sodium diuresis (C(Na)/GFR>0.1) are plotted on the same graph, glucose reabsorption at any given glomerular filtration rate is much less than during antidiuresis. Glucose reabsorption divided by glomerular filtration rate varies inversely with fractional sodium excretion. This study demonstrates that glomerular tubular balance for glucose exists in the dog and that this balance is changed when sodium reabsorption changes.